POETIC-SEMANTIC FUNCTIONS OF FLOWER NAMES IN ENGLISH AND UZBEK FICTION: A COMPARATIVE LINGUOCULTURAL STUDY (American Journal of Pedagogical and Educational Research, 2026)
This article investigates the poetic-semantic functions of flower names in English and Uzbek fiction through comparative, linguocultural and cognitive analysis. The study focuses on the symbolic, metaphorical, aesthetic and conceptual roles of floronyms in literary discourse. Drawing on examples from English and Uzbek poetry and prose, the paper argues that flower names function not simply as lexical nominations but as culturally and conceptually loaded poetic signs. The analysis reveals both universal symbolic patterns and nationally specific semantic features embedded in floral imagery. The findings contribute to comparative linguistics, linguistic poetics and conceptual studies by demonstrating how floronyms participate in the representation of artistic worldview.